Saúde pública e controle social: um estudo de caso do conselho municipal de saúde de Uberlândia CMSU no período de 1991 - 2013 - Pereira, Florence Rocha Verçosa (2013)
Public health as a social policy is consolidated through participation and popular control. Thus, it is through the observation of Boards of Health, specifically the Municipal Health Council of Uberlândia- CMSU since its inception in 1991 until the year 2013, that this case study proposes to understand to what extent it can be said that there is the existence of a \"Social Control\". The question that guided the study was: are there no institutionalized political participation in these spaces that allows us to affirm the existence of a new form of democracy through popular participation? The objective of this research was to analyze the ability of the deliberative and purposeful CMSU in relation to public health policie sand democratization of these spaces, in view of the general decisions about the health of the city. This was a qualitative study that was guided by the document analysis, literature research and field work, through the application of semi-structured interviews that took place with the consent of respondents between May and April 2013. The subjects were members of the Board of Health of Uberlândia CMSU. The results show: difficulty in performing the training courses; the transfer of information to society is not satisfactorily; there is alack of channels of communication for these purposes; the participation of the diretors mostly happened through the appointment of the manager and is still being done so; there are difficulties regarding transportation; load-time of dedication, dynamic and hours of operation of the meetings of CMSU. In general, all advisors surveyed evaluated positively their participation and feel satisfied whilecounselors. This work aims to show the scope and limits of the SUS regarding public participation, because it is accepted that the power and decisions in the hands of its biggest stakeholders, the public, can be better managed. It is concluded that the proposed health councils exercising social control is a breakthrough in ensuring public health, because it acts vigilantly in public spending in the budget given and in the deliberations of the general health of the city.